Maxillary Central Incisor and Canine Odontometrics: An Obscure Tool for Sex Determination in the Indian Demographic (Journal of Forensic Medicine & Toxicology, 2026)
The aim of the study was to determine the mean values of cervico-incisal and mesio-distal odontometrics of maxil lary central incisors and maxillary canines among the Indian population; and investigate whether any significant sexual  dimorphism (P value < 0.05) exists among them. The objective was also to discover the significant sexually dimorphic  odontometric parameters in different age groups among the study population. Relationship of these odontometrics with  the age of the subjects was also assessed. This cross-sectional study consisted of 104 subjects (54 males and 50 females).  In each participant, cervico-incisal and mesio-distal odontometric dimensions of permanent maxillary central incisors  and maxillary canines of both sides (CI11, MD11, CI21, MD21, CI13, MD13, CI23, MD23) were calculated intraorally,  using a digital vernier caliper. Data obtained was then statistically analyzed using SPSS version 21.0. Six odontometric  measurements were significantly greater in males than in females in the overall study population. CI23 emerged as the  most reliable odontometric parameter. Specific significant odontometric parameters were also found in every age group  among the study population. No significant relationship between any odontometric dimension and the age of participants was observed. It was revealed that the cervico-incisal odontometric measurements of maxillary central incisors  and canines, and mesio-distal odontometric measurements of maxillary canines, can play a notable role in determining  sex within the Indian population. Findings of this research can assist forensic odontologists in utilizing specific odon tometric parameters to ascertain the sex of individuals, when their age range is known and they are part of the Indian  demographic.
Keywords: Dental anthropology; Disaster victim identification; Odontometrics; Sexual dimorphism